2004
DOI: 10.1081/copd-120039809
|View full text |Cite
|
Sign up to set email alerts
|

Economic Impact of Pulmonary Drugs on Direct Costs of Stable Chronic Obstructive Pulmonary Disease

Abstract: Annual direct costs were 1,657 EUR in stage I, 2,425 EUR in stage II, and 3,303 EUR in stage III. The mean direct costs was 2,061 EUR (38% corresponded to drug therapy). Medication accounted for 43%, 37.6%, and 28.4% of total direct costs for stage I, II, and III, respectively. Inhaled steroids and long-acting beta2-agonists accounted for 78%, 76%, and 75% of total drugs costs in stages I, II, and III, respectively. Drug therapy which was not in accordance with guidelines accounted for 78.7% and 54% of total d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
21
1
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 21 publications
6
21
1
6
Order By: Relevance
“…[11][12][13][14]34 These costs are not comparable, due to differences in the healthcare systems and methodologies involved. The mean cost in our series is higher than that in studies with similar methodologies and unit prices, 11,12 especially due to baseline treatments (basically inhalers and inhaled Oral antibiotics pooled costs is the sum of costs of all courses of antibiotics that each patient needed for exacerbation during the year. c Exacerbations pooled costs is the sum of costs of all the emergency room visits, hospital admissions and courses of antibiotics that each patient required for exacerbation during the year.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14]34 These costs are not comparable, due to differences in the healthcare systems and methodologies involved. The mean cost in our series is higher than that in studies with similar methodologies and unit prices, 11,12 especially due to baseline treatments (basically inhalers and inhaled Oral antibiotics pooled costs is the sum of costs of all courses of antibiotics that each patient needed for exacerbation during the year. c Exacerbations pooled costs is the sum of costs of all the emergency room visits, hospital admissions and courses of antibiotics that each patient required for exacerbation during the year.…”
Section: Discussionmentioning
confidence: 99%
“…The few studies published to date on the costs associated with BE show that these are high, [8][9][10] and possibly greater than those described for chronic obstructive pulmonary disease (COPD). [11][12][13][14] Since most of the direct costs of the BE management can be attributed to exacerbations and baseline treatment, 15,16 it is reasonable to suppose that more severe patients give rise to higher health costs. This is an important topic, in the light of the current levels of diagnosis, 17,18 hospitalization and mortality 10,19 of BE patients.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from the possible comparison with the GOLD guidelines, various studies in recent years have estimated the economic burden of this disease in Spain, showing that the total annual direct cost of COPD per patient varies between €1100 and €3400, with a mean of approximately €2000 [Miravitlles and Figueras, 2001;Miravitlles et al 2003;de Miguel Díez, 2005;Masa et al 2004;Izquierdo-Alonso and de Miguel-Díez, 2004;de Miguel Díez et al 2008]. In our study we found the costs for patients with stage II disease to be in line with previous estimations, but the direct cost observed for patients with stage III disease was around €1900 higher than the average.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 1.3 (SD 4.7) are to specialists, 0.7 (SD 3.0) to emergency services and patients spend an average of 1 day in hospital (SD 5.3) [Izquierdo-Alonso and de Miguel-Díez, 2004]. From these figures, it was estimated that a sample of 624 patients would allow a difference of 2 days to be detected in the calculation of the mean total number of visits, assuming a maximum SD of 25.5 days and a confidence interval of 95%.…”
Section: Sample Sizementioning
confidence: 99%
“…17 utilizando como año base 2010, para EPOC se usan los datos de Izquierdo y cols. 18 , utilizando como año base 2004; y para la diabetes se usan los datos de Mata et al 19 …”
Section: Estimación De Los Costes Potencialesunclassified